Correlation between neutrophil/lymphocyte ratio and cognitive impairment in cerebral small vessel disease patients: A retrospective study - Hou, Lan; Zhang, Shuhan; Qi, Dandan; Jia, Tongle; Wang, Huan; Zhang, Wei; Wei, Shuyan; Xue, Conglong; Wang, Pei (Frontiers in Neurology, 2022)
Background and objective The blood neutrophil/lymphocyte ratio (NLR) is an objective and convenient parameter of systemic inflammation. Elevated NLR is associated with an increased risk of mild cognitive impairment (CI) in the elderly. However, few data are available on the impact of the NLR on CI in patients with cerebral small vessel disease (CSVD). Methods A total of 66 CSVD subjects with CI and 81 CSVD subjects without CI were evaluated in this study. Clinical, laboratory, radiological, and cognitive parameters were collected. The NLR was obtained with the absolute neutrophil count being divided by the absolute lymphocyte count in fasting blood samples. Logistic regression analysis was performed to evaluate the factors associated with CI. Receiver operating characteristic curves were illustrated to predict factors associated with CI in patients with CSVD. Results The NLR of the CI group was significantly higher than that of subjects without CI (2.59 vs. 2.21, P = 0.003). In multivariate analysis, NLR was positively correlated to the CI (OR: 1.43, 95% CI: 1.05–1.96, P = 0.024). It was suggested that the optimum NLR cutoff point for CI was 1.89 with 69.7% sensitivity and 59.3% specificity. Subjects with NLR ≥ 1.89 showed higher possibilities of CI compared to those with NLR < 1.89 (OR: 3.38, 95% CI: 1.62–7.07). Conclusions Correlations were found between NLR and CI. Patients with CSVD who have higher NLR might have an increased risk of CI.